2016
DOI: 10.1017/s0031182016002377
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial cell wall biosynthesis: a multifaceted antibiotic target

Abstract: S U M M A R YMycobacterium tuberculosis (Mtb), the etiological agent of tuberculosis (TB), is recognized as a global health emergency as promoted by the World Health Organization. Over 1 million deaths per year, along with the emergence of multi-and extensively-drug resistant strains of Mtb, have triggered intensive research into the pathogenicity and biochemistry of this microorganism, guiding the development of anti-TB chemotherapeutic agents. The essential mycobacterial cell wall, sharing some common featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
146
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(146 citation statements)
references
References 210 publications
(264 reference statements)
0
146
0
Order By: Relevance
“…6,7 Due to the role of the cell wall in both bacterial survival and pathogenesis, those enzymes involved in its biosynthesis have been and continue to be targets for drug design.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Due to the role of the cell wall in both bacterial survival and pathogenesis, those enzymes involved in its biosynthesis have been and continue to be targets for drug design.…”
Section: Introductionmentioning
confidence: 99%
“…The Mycobacterium genus encompasses not only human pathogens that have enormous impact on global health (i.e., Mycobacterium tuberculosis, M. leprae), but also the saprophytic species, such as Mycobacterium smegmatis, which is a model organism for studies on the cell biology of tubercle bacilli. Mycobacteria possess a unique multilayered cell envelope and, unlike other rod-shaped bacteria, incorporate peptidoglycan precursors at their cell tips (Abrahams & Besra, 2018;GarcĂ­a-Heredia et al, 2018;B. Singh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] The complex lipids and glycans within the cell envelope provide a formidable, impermeable barrier to antibiotics that further complicates efforts to eradicate TB. [2][3][4][5] The architecture of the Mtb cell envelope comprises a complex macromolecular core consisting of peptidoglycan linked to arabinogalactan that in turn is covalently attached to long-chain mycolic acids (mAGP complex). 3 Additional non-covalently linked lipids and lipoglycans are interspersed within the mycolate layer of the mAGP complex to form an outer, waxy, 'mycomembrane'.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] The current anti-tubercular agents are lethal to Mtb through modulation of well-defined intracellular pathways. 6 In particular, targeting key enzymes that are involved in the synthesis and assembly of the Mtb cell envelope has proved to be a highly effective strategy for the development of new TB therapeutics, 5,6 highlighted by the clinical use of the frontline antitubercular agents isoniazid and ethambutol and several second-line drugs that include cycloserine and ethionamide. [7][8][9] Recent studies have shown that an alternative anti-tubercular approach is possible through the direct capture of the structurally unique mycobacterial extracellular glycans with multimeric boronic acids.…”
Section: Introductionmentioning
confidence: 99%